2022
DOI: 10.3390/math10010147
|View full text |Cite
|
Sign up to set email alerts
|

Sufficient Conditions for Some Stochastic Orders of Discrete Random Variables with Applications in Reliability

Abstract: In this paper we focus on providing sufficient conditions for some well-known stochastic orders in reliability but dealing with the discrete versions of them, filling a gap in the literature. In particular, we find conditions based on the unimodality of the likelihood ratio for the comparison in some stochastic orders of two discrete random variables. These results have interest in comparing discrete random variables because the sufficient conditions are easy to check when there are no closed expressions for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…A number of papers [11][12][13][14][15][16][17][18][19][20][21][22] contain relevant results on this issue. Recent research concerning stochastic orders of discrete random variables can be found in [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of papers [11][12][13][14][15][16][17][18][19][20][21][22] contain relevant results on this issue. Recent research concerning stochastic orders of discrete random variables can be found in [23].…”
Section: Introductionmentioning
confidence: 99%
“…Our description of the residual life variance and inactivity time variance follows the approach in [25] for the failure rate and that in [26] for the reversed hazard rate in mixtures. Both studies present a Bayesian perspective, based on the conditional distribution of the frailty given the data, which is different from that in [2][3][4][6][7][8][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Hence, the frailty cannot be observed but it can be updated.…”
Section: Introductionmentioning
confidence: 99%